Acesso efetivo à justiça e a implantação dos juizados especiais federais no Brasil - Miguel, Alexandre (2006)
The effectiveness of civil rights demands efficient judicial instruments able to protect them under the courts. For that reason, modern constitucionalism started considering the admission on court (“a day at a court”) as a basic human right. The Brasilian Federal Constitution followed such a tendency, adopting the mentioned right as fundamental (article 5, XXXV). The simple formal guarantee of admittance on court established by the liberal states on the XVIII and XIX century is not enough to assure the concrete protection to this fundamental guaranty. From the meddle of XX century ahead, particularly on the west countries, the right to be admitted on court begun to be strengthed by technics cronologicaly implanted - the so called waves. The first wave was the legal assistance for the poors. The second wave was the protection to the transindividual interests (diffuse rights). The third wave takes under consideration the previous moviments, but goes further, defending a new conception of acess to the court, rebuilding the civil procedure, adopting alternative methods of judgment, creating special procedures to certain types of socially relevant cases, changing the judiciary services itselves, and simplifying the civil rights. On Brazil, one of the most amazing experiment on this new vision about acess to justice happened on the project very well succeed of the “juizados de pequenas causas” (“small claims courts”), specially the federal ones, by the social relevance of their cases, usually keeping national attention. Before them, there was a huge financial obstruction for the solution of such cases, besides the considerable time for the procedure to be finished, on those simple cases envolving the federal government and other federal entities. This present work deals with the fundamental right of acess to justice on its relationship with the small claims federal courts. The objective of it is to explore the effectiveness of those courts on its mission of improving the real and substantive acess to justice on federal jurisdiction, by adopting a theoric and an empiric approach. The approach method is deductive and the procedural method is empirc and statistician, using documental technics and bibliographic researchs. The results obtained on the development of this work show how important are the small claims federal courts nowadays, as an instrument of justice, for the poorest portion of the brazilian population, assuring them a real protection for their